Acute cognitive workload hampers subjective recovery, but does not accelerate exhaustion in a maximal effort test on a treadmill - Sanchez-Delgado, G.; Conde-Gonzalez, J.; Perales, J. C.; Pinar, M. I.; Cárdenas, D.; de Teresa-Galvan, C.; Ruiz, J. R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Aim: The aims of the present study were: (1) To investigate the effect of acute mental workload on time-to-exhaustion and perceived exertion in a concomitant maximum effort test on a treadmill. And, secondly, (2) to check whether physical effort and recovery modulated performance in the mental workload task. Methods: The physical load task was an incremental maximum effort test on a treadmill, followed by an 8-minutes recovery period. The mental workload task was a working memory task (N-back), with two modalities: a highly loading one (3-back), and a less loading one (1-back). 14 men (aged 18-22) went through 5 conditions, run in counterbalanced order: 1) Physical load/high mental workload; 2) Physical load/low mental workload; 3) Physical load/no mental workload; 4) No physical loadhigh mental workload; 5) No physical load-low mental workload. Conditions 1-3 were carried out on the treadmill, and varied in the degree of mental workload. Conditions 4 and 5 included no physical task, and varied in the degree of mental workload. We measured time-to-exhaustion in conditions 1, 2 and 3. After every two minutes, participants reported their perceived exertion (RPE-CR10). In conditions 1, 2, 4 and 5, we registered accuracy in the cognitive task. Results: Mental workload had no effect on time-to-exhaustion in conditions 1-3 (M=683.28s, 711.00s, and 681.07s.; SE=32.47s, 36.44s, and 36.07s, respectively). Perceived exertion during effort did not differ across those conditions either (M=6.79, 6.93, and 6.52; SE=.43, .41, and .47). However, perceived exertion during recovery was affected by mental workload [M=2.21, 2.35, and 2.52; SE=.17, .21, and .23; F(2,26)=2.38, p<.01], and perceived exertion decreased more slowly as mental workload increased [F(10,130)=3.96, p<.01, for the relevant interaction]. Physical effort hampered performance in the mental workload task. Considering conditions 1, 2, 4, and 5, the difference between physical load conditions (1, 2) and no physical load conditions (3, 4) was maximal around the exhaustion point .17 points for the difference between conditions 4 and 5, and .27 points for the difference between conditions 1 and 2, F(7, 91)=4.03, p<.01, for the corresponding interaction]. Performance in the mental workload task was always above chance. Conclusions: i) concomitant mental workload did not accelerate exhaustion, yet slowed subjective recovery down; ii) the presence of physical workload affected performance in a concomitant cognitive, mentally loading task, without causing complete disengagement from it.